A frailty index predicts survival and incident multimorbidity independent of markers of HIV disease severity. (24th August 2015) - Guaraldi, Giovanni; Brothers, Thomas D.; Zona, Stefano; Stentarelli, Chiara; Carli, Federica; Malagoli, Andrea; Santoro, Antonella; Menozzi, Marianna; Mussi, Chiara; Mussini, Cristina; Kirkland, Susan; Falutz, Julian; et al.
<x xml:space="preserve">Abstract</x> Objectives: Aging with HIV is associated with multisystem vulnerability that might be well characterized by frailty. We sought to construct a frailty index based on health deficit accumulation in a large HIV clinical cohort and evaluate its validity including the ability to predict mortality and incident multimorbidity. Design and methods: This is an analysis of data from the prospective Modena HIV Metabolic Clinic cohort, 2004–2014. Routine health variables were screened for potential inclusion in a frailty index. Content, construct, and criterion validity of the frailty index were assessed. Multivariable regression models were built to investigate the ability of the frailty index to predict survival and incident multimorbidity (at least two chronic disease diagnoses) after adjusting for known HIV-related and behavioral factors. Results: Two thousand, seven hundred and twenty participants (mean age 46 ± 8; 32% women) provided 9784 study visits; 37 non-HIV-related variables were included in a frailty index. The frailty index exhibited expected characteristics and met validation criteria. Predictors of survival were frailty index (0.1 increment, adjusted hazard ratio 1.63, 95% confidence interval 1.05–2.52), current CD4+ cell count (0.48, 0.32–0.72), and injection drug use (2.51, 1.16–5.44). Predictors of incident multimorbidity were frailty index (adjusted incident rate ratio 1.98, 1.65–2.36), age (1.07, 1.05–1.09), female sex (0.61, 0.40–0.91), and current CD4+ cell count (0.71, 0.59–0.85). Conclusion: Among people aging with HIV in northern Italy, a frailty index based on deficit accumulation predicted survival and incident multimorbidity independently of HIV-related and behavioral risk factors. The frailty index holds potential value in quantifying vulnerability among people aging with HIV.